A Comparative Behavioral Investigation into Trust and Reciprocity using the Trust - HAZIK MOHAMED (International Journal of Islamic Economics and Governance, 2020)
This paper discusses the importance of trust to economic transactions and risk-mitigation, and investigates the degree of compliance of individual behaviors to engender trust and reciprocity, through a behavioral approach, to understand the pervasiveness of such essential economic ethic in everyday economic transactions.The methodology of this study assesses the behavior of the subject pool (players representative of Muslims and non-Muslims) through a Trust Game that was designed to test how entrenched trust and reciprocity are in modern societies. The game is an experiment in decision-making to measure trust in economic decisions and to demonstrate that trust is as fundamental to economic transactions as self-interest. The concept of trust and reciprocity can be complex when taken into account its relationship with risk that is not readily quantified, especially in a highly uncertain situation. For this experiment, in terms of trust and reciprocity, both Muslims and non- Muslims performed well, although Muslims performed a little bit better than non-Muslims. There were no significant differences between the primed and unprimed subjects. While empirical studies have demonstrated the importance of trust and ethics in economic development, they do not demonstrate how deep religious understanding in human behavior for mutually beneficial decision-making. This paper attempts to address this concern so as to use religious values in productive economic behaviors, like mitigating risk in uncertainty through trust and reciprocity in risk-sharing. This paper provides an actual behavioral investigation into how people behave in real life as compared to what their religion prescribes to them.